Log in

Connect faster with


Signup faster with

|   Education without borders.
a Guest

{(a-b)-x}sqr + {(b-a)-y}sqr = {(a-b)-x}sqr + {(a+b)-y}sqr

Posted in Math, asked by rahul maurya, 6 years ago. 1657 hits.


{(a-b)-x}^2 + {(b-a)-y}^2 = {(a-b)-x}^2 {(a+b)-y}^2

first term of both sides will be cancel out

therefore, {(b-a)-y}^2 = {(a+b)-y}^2

open the term by the formula (a-b)^2 = a^2+b^2-2ab

(b-a)^2 + y^2 -2(b-a)y = (a+b)^2 + y^2+2(a+b)y

y^2 will be cancel out from both sides

now open all the braces

b^2+a^2-2by + 2ay = a^2 + b^2 +2ab +2ay +2by

on solving  we get

-2b(a+y) = 2b(b+y)

-(a+y) = (b+y)

-a-b = y-y

therfore.       a = -b    ANS.

priyanka sharma
priyanka sharma - 6 years ago
Ask priyanka sharma for further help.
Please register/login to answer this question. 
- Just now


a Guest
Just now
× Attachments/references, if any, will be shown after refreshing the page.